A scalable CRISPR/Cas9-based fluorescent reporter assay to study DNA double-strand break repair choice - Roidos, Paris; Sungalee, Stéphanie; Benfatto, Salvatore; Serçin, Özdemirhan; Stütz, Adrian M.; Abdollahi, Amir; Mauer, Jan; Zenke, Frank T.; Korbel, Jan Oliver; Mardin, Balca R. (Nature Communications, 2020)
Double-strand breaks (DSBs) are the most toxic type of DNA lesions. Cells repair these lesions using either end protection- or end resection-coupled mechanisms. To study DSB repair choice, we present the Color Assay Tracing-Repair (CAT-R) to simultaneously quantify DSB repair via end protection and end resection pathways. CAT-R introduces DSBs using CRISPR/Cas9 in a tandem fluorescent reporter, whose repair distinguishes small insertions/deletions from large deletions. We demonstrate CAT-R applications in chemical and genetic screens. First, we evaluate 21 compounds currently in clinical trials which target the DNA damage response. Second, we examine how 417 factors involved in DNA damage response influence the choice between end protection and end resection. Finally, we show that impairing nucleotide excision repair favors error-free repair, providing an alternative way for improving CRISPR/Cas9-based knock-ins. CAT-R is a high-throughput, versatile assay to assess DSB repair choice, which facilitates comprehensive studies of DNA repair and drug efficiency testing.
Gesehen am 22.10.2020